TELEMONITORAMENTO EM PACIENTES COM FATORES DE RISCO PARA DESENVOLVEREM EVENTOS CARDIOVASCULARES - FERREIRA OLIVEIRA , ALINE EMANUELE; FREITAS , VIVIANE PAULA; SOARES CAMPOS , KEROLYNNE; HERÉDIA LUZ , HIAGO DANIEL; GOMES FERNANDES , BIANCA; SOUZA E SILVA , KETELIYN RAYSSA; BRAGA SCLAUSER PESSOA , ISABELA MARIA (Sinapse Múltipla, 2019)